Understanding students' behavior on the use of online social networking - Masrom, Maslin; Usat, Selisa (2013)
The purpose of this research is to review current published research studies focusing on the use of Facebook by students.The focus of this research review is only limited to the empirical studies of the use of Facebook because it is the most popular Online Social Networking (OSN) among students. The qualitative approach was employed for this research.The results indicated that there were only few past studies found to be related to OSN studies among students in Malaysia.However, there was lack of published empirical-based studies specifically on school students‘ OSN use in Malaysia found from the past studies.The results also revealed that the current published studies on OSN in Malaysia are only focused mainly on college or university students